Mineral profile in the plasma offree ranging camels (Camelus dromedarius) in Kenya - Kuria, SG; Gachuiri, C K; Wahome, RG; Wanyoike, M M (The Indian Journal of Animal Sciences, 2011)
The levels of important macro and trace minerals were assessed in the plasma oflactating camels kept by pastoralists in Kenya. The average plasma Ca and Na concentrations were below while mean concentration for K, P, Fe, Zn and Co were within the reported range. Mg concentration was above the reported range. Plasma concentration of Ca, K, Na and Zn decreased from dry to wet season, and of Mg, P and Co increased. Plasma Fe and Co were same in both seasons. Other factors that may affect the plasma concentration of these minerals were also assessed.Â